A study of local customer perception on quality of counter services provided by Tabung Haji (TH) / Suhaini Mat Daud - Mat Daud, Suhaini (1999)
Lembaga Tabung Haji (TH) or the Pilgrims Fund Board was established 36 years ago as an institutions which responsible in providing an appropriate Islamic means of mobilizing savings and preventing the fragmentation of wealth by assisting Muslims to perform the hajj at Mecca without impoverishing them of any financial burden or hardship after their pilgrimage. After 36 years of establishment, TH has now revolutionized its’ functions to be more competitive and comprehensive. The emergence of superior technologies has led TH to be one of the most established financial institutions in Malaysia. This study focused on the local customer perceptions on quality of counter services provided by TH, which emphasizes in Besut area only. The main objective of this research is to know about customers perception towards counter services offered, the level of quality according to services provided and counter services compared to other financial institutions located in Besut area. Hopefully, this study also enables TH to seek and eventually change customer perceptions from negative perceptions to positive perceptions. From the data analysis and findings, there are some recommendations suggested to be implemented by company like formulate training program to the staff, create attractive and creative promotion strategy and so forth.